Discourse of Self-Presentation in Academic Communicative Space - L. G. Vikulova; O. I. Korolenko; Yu. G. Tkachenko (Научный диалог)
This article examines the genre of the welcoming speech — elogioum — established within the speech practices of the French Academy as a discursive community. The empirical material selected for this study is the text of Barbara Cassin’s eulogistic speech for Philippe Bossan. A discursive-analytical approach to the research allows for the identification of the communicative structure and genre classification of the text, as well as an exploration of the conceptual strategies employed in Cassin’s public address, which is analyzed as a form of self-presentation within the context of her election to the French Academy. At the level of meanings conveyed by the speaker, intersections among various discourses are revealed, including philosophical, musical, political, philological, historical, migratory, familial, and mythological discourses, each marked by recognizable linguistic markers that indicate the interdiscursive nature of the speech. It is established that the perlocutionary effect of the elogioum manifests in the political orientation of Cassin’s discourse, which calls for changes in Europe’s language and migration policies. The research employs interpretive, conceptual methods along with elements of quantitative analysis.